Play is a play, is a play, is a play… or is it? Challenges in designing, implementing and evaluating play-based interventions - Bodrova, Elena; Leong, Deborah Jane; Yudina, Elena (Frontiers in Psychology, 2023)
When a social-emotional learning (SEL) intervention is implemented in an early childhood classroom, it often involves play. Some interventions even list play as its main component. However, the advocates of play arguing for the return of play in early childhood education (ECE) classrooms still have difficulty convincing the proponents of more rigorous academic instruction. These proponents cite research pointing to the insufficient evidence of the positive effect of play on children’s short- and longer-term social, emotional, cognitive, and behavioral outcomes as well as their overall well-being. We believe that there are multiple issues with play-based interventions’ design, implementation, and evaluation that might account for this insufficient evidence. In our paper, we discuss the numerous ways play does (or does not) feature in SEL interventions and how it might affect the outcomes of these interventions. We also examine the methodological challenges of having child-controlled play as a component of an SEL intervention. While we are not proposing a specific protocol for re-evaluation of the results of existing interventions, we outline some ways such re-evaluation can be possible in the future, along with the development and evaluation of new play-based SEL interventions.